KUALITAS HASIL TANAMAN PADI (Oriza sativa L.) VARIETAS INPARI 32 : INTERVAL WAKTU INDUKSI DAN PEMBERIAN GIBERELIN DENGAN SISTEM INTENSIFIKASI POTENSI LOKAL (SIPLO) - adrian kurniawan; Siti Muslikah; Sugiarto Sugiarto (AGRONISMA, 2022)
Rice (Oriza sativa L.) is a food crop that has important meaning for almost the entire population of Indonesia because rice is able to meet the caloric needs of most of the Indonesian population. SIPLO (Local Potential Intensification System) is the local potential of the soil by electrical induction/stimulation into the soil to balance the positive and negative charges of the soil, which plays an important role in providing soil nutrients. This research was conducted in Jatisari Village, Pakisaji District, Malang Regency. With an altitude of 395 m above sea level. The study was carried out from November 2021 - March 2022. This research was conducted using the Factorial Randomized Block Design (RAK) method, which consisted of 2 factors, the first factor consisted of 2 types and the second factor consisted of 2 types with 3 replications. The combination of SIPLO induction time interval treatment and the administration of ZPT GA3 had a significant effect on some of the observed parameters measured. The best treatment was found in the combination of H2Z2 (induction time interval every 6 days + giving ZPT GA3 22gr/ha). The SIPLO induction time interval has a significant effect on the measured, the best treatment is in the H2 treatment (induction interval every 6 days). Giving ZPT GA3 had a significant effect on several parameters measured, the best treatment was in treatment Z2 (giving PGR GA3 22gr/ha).Keywords: Rice, Inpari 32, SIPLO, ZPT Gibberellins